Harvesting of Microalgae Biomass using Bio-flocculant - Ahmad Nazmi, Amirah (Universiti Teknologi PETRONAS, 2016)
Microalgae biomass provides an alternative solution for renewable energy. However, the cost of the harvesting process is expensive. Hence, in the present study, the potential of cultivating microalgae (Chlorella vulgaris) was explored using a less expensive and environmental-friendly solution, bio-flocculant. At the preliminary stage, a few natural products were chosen and extracted to produce bioflocculants. The suitability of the natural resource were ensured that they are good bio-flocculants. In separate experiments, the microalgae were cultivated at optimum condition. The bio-flocculants namely chitosan, okra and moringa oleifera were jar tested with the microalgae. The jar test involves parameters dosage, pH value, and stirring speed against the efficiency of harvesting of microalgae biomass. The result of the harvest proves that chitosan is a better bio-flocculant than moringa oleifera but both can be used as bio-flocculants.